2013
DOI: 10.1111/cmi.12123
|View full text |Cite
|
Sign up to set email alerts
|

Erythrophagocytosis of desialylated red blood cells is responsible for anaemia duringTrypanosoma vivaxinfection

Abstract: SummaryTrypanosomal infection-induced anaemia is a devastating scourge for cattle in widespread regions. Although Trypanosoma vivax is considered as one of the most important parasites regarding economic impact in Africa and South America, very few in-depth studies have been conducted due to the difficulty of manipulating this parasite. Several hypotheses were proposed to explain trypanosome induced-anaemia but mechanisms have not yet been elucidated. Here, we characterized a multigenic family of trans-sialida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 57 publications
2
55
1
Order By: Relevance
“…There was a steady decrease in the erythrocyte count, hemoglobin and PCV, although they remained within the reference values. Decreases in erythrocytes have been associated with erythrocytes desialylation in the acute phase of disease, stage of high parasitemia (GUEGAN et al, 2013). Our findings differ from those obtained by other authors in cattle BATISTA et al, 2007BATISTA et al, , 2008CUGLOVICI et al, 2010;CADIOLI et al, 2012) who noticed moderate to severe anemia.…”
Section: Discussioncontrasting
confidence: 97%
“…There was a steady decrease in the erythrocyte count, hemoglobin and PCV, although they remained within the reference values. Decreases in erythrocytes have been associated with erythrocytes desialylation in the acute phase of disease, stage of high parasitemia (GUEGAN et al, 2013). Our findings differ from those obtained by other authors in cattle BATISTA et al, 2007BATISTA et al, , 2008CUGLOVICI et al, 2010;CADIOLI et al, 2012) who noticed moderate to severe anemia.…”
Section: Discussioncontrasting
confidence: 97%
“…Both cytokines are thought to promote the development of anemia and immunopathology, but also to regulate parasitemia and prolong survival. Additionally, IL-10 is shown to mediate survival of the mice by limiting inflammatory complications, supporting a protective role for IL-10 in hyperinflammation as suggested in animal models for primary HLH [99,[104][105][106][107][108][109].…”
Section: Parasitic Infectionmentioning
confidence: 55%
“…The biological role of TvTS1 is less well defined. Evidence presented by Guegan et al (2013) suggests that TvTS1 may play a role in T. vivax-associated anaemia, although this hypothesis requires further investigation. Study of the structure-function relationship of TvTS1 will help in grasping its biological function during bloodstream T. vivax parasite infections and might serve as the basis for the development of an antipathology treatment.…”
Section: Figurementioning
confidence: 97%
“…In T. cruzi, the only intracellular trypanosome, it has been shown that its transsialidases play a role in host-cell invasion, parasite virulence and immune suppression (Schenkman et al, 1992;Buschiazzo et al, 2002;Jacobs et al, 2010;Giorgi & de Lederkremer, 2011). In T. vivax infections, trans-sialidase activity has been proposed to be linked to the typically observed severe anaemia (Bratosin et al, 1998;Buratai et al, 2006;Guegan et al, 2013). Hence, for disease-associated trypanosomal transsialidases, unravelling their structure-function relationship might yield insights into the molecular mechanisms behind the onset of trypanosomosis-induced pathologies.…”
Section: Introductionmentioning
confidence: 99%